Exploring Arabic Synonyms for Beginner Learners: A Vocabulary-Based Approach - Segaf Baharun; Nur Hanifansyah (Universitas KH. Mukhtar Syafaat, 2026)
Abstract: This study explores the pedagogical role of synonym-based vocabulary instruction in Arabic language learning for beginner students. Vocabulary is widely recognized as the foundation of second language acquisition, yet the systematic teaching of synonyms has received limited attention in Arabic pedagogy. The aim of this study is to investigate how synonyms can be effectively introduced to novice learners and to assess their impact on lexical competence and communicative readiness. Employing a qualitative descriptive approach, the research was conducted at Pondok Pesantren Darullughah Wadda’wah, Pasuruan, Indonesia, with a focus on 30 newly enrolled students who had minimal prior exposure to Arabic. Data were collected through classroom observations, semi-structured interviews, and focus group discussions with students, as well as teacher interviews and supporting teaching materials. Thematic analysis, based on Miles and Huberman’s framework, identified three key findings: first, semantic grouping of synonyms such as ???–???, ???–???, and ???–???? enhanced students’ comprehension of nuanced meanings; second, synonym learning improved vocabulary recall by associating multiple words with a single concept; and third, students expressed greater confidence and inclusivity in oral communication when exposed to lexical alternatives. The results confirm that synonym-based instruction is not merely an enrichment activity but a fundamental strategy to deepen lexical knowledge and foster communicative competence at the beginner level. This study contributes to bridging the gap between semantic theory, computational approaches to synonymy, and practical pedagogy, offering practical implications for Arabic curriculum design and classroom practice.